Exploring the morphology of flax fibres by X-ray microtomography and the related mechanical response by numerical modelling. (September 2022) - Richely, E.; Bourmaud, A.; Dhakal, H.; Zhang, Z.; Beaugrand, J.; Guessasma, S.
Highlights: The flax fibre morphology was studied by high resolution X-ray microtomography. The morphology-mechanical property relationship was assessed by finite element analysis. A decrease in stiffness linked to the porosity and intricate shapes is reported. Stress concentrations seem induced by surface roughness and internal porosities. Abstract: The external shape and internal lumen of flax fibres are investigated using X-ray microtomography (µ-CT) and finite element (FE) modelling. µ-CT reveals an intricate flax fibre and lumen morphology, with mean porosity contents between 0 and 7.2%. The FE model is based on 3D volumes obtained by X-ray µ-CT and tensile testing in the elastic domain. Numerical results demonstrate the decrease of stiffness as a combined effect of porosity and stress heterogeneity triggered by geometrical considerations. Moreover, stress concentrations induced by both surface roughness and complex lumen shape were observed, highlighting their possible implication in failure mechanisms. However, Young's moduli are overestimated compared to experimental curves and non-linearities are not considered by the rather strong hypothesis of this model (linear elastic material: no viscosity, plasticity or damage mechanisms taken into account). Future work should include the orientation and reorientation of cellulose microfibrils upon tensile testing, as well as damage mechanisms.